2022
DOI: 10.31234/osf.io/wbjyc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using a foreign language does not make you think more: Null effects of using a foreign language on cognitive reflection and numeracy

Abstract: Using a foreign language is suggested to affect how we think and decide, even reducing bias in our judgment. However, the exact mechanisms of its influence are still unknown. In this project, we tested two of the potential mechanisms driving the foreign language: increased cognitive reflection and greater task engagement. We analyzed previously collected data from 5 experiments employing the Cognitive Reflection Test and/or the Berlin Numeracy Test. The results show anecdotal to strong evidence supporting null… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…In other words, we found that the Language × News Type interaction was not moderated by cognitive reflection (Experiments 1 and 2), familiarity with news, or perceived arousal (Experiment 1). Of course, our study could be underpowered to detect such effects; however, our results are consistent with studies showing that FLe is robust to emotions (Chan et al, 2016; Geipel et al, 2015a; Muda, Walker, et al, 2020) and does not affect cognitive reflection scores (Milczarski et al, 2022). Hence, our data do not support the decreased-affect and increased-reflection models.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In other words, we found that the Language × News Type interaction was not moderated by cognitive reflection (Experiments 1 and 2), familiarity with news, or perceived arousal (Experiment 1). Of course, our study could be underpowered to detect such effects; however, our results are consistent with studies showing that FLe is robust to emotions (Chan et al, 2016; Geipel et al, 2015a; Muda, Walker, et al, 2020) and does not affect cognitive reflection scores (Milczarski et al, 2022). Hence, our data do not support the decreased-affect and increased-reflection models.…”
Section: Discussionsupporting
confidence: 88%
“…More recent research found that decisionmakers do not always benefit from using their FL: using a FL does not affect decision-making in gambling (Muda, Walker, et al, 2020), intertemporal choice (Białek et al, 2022; Xu et al, 2021), and may not increase reflective thinking (Jensen Mækelæ & Pfuhl, 2019; Milczarski et al, 2022). There is also evidence that using a FL does not make people think more (i.e., using a FL does not result in increased cognitive reflection or greater task engagement, Milczarski et al, 2022) and may even distort the ability to detect when a salient intuition might be wrong (Białek et al, 2020). That is, people may have limited access to their intuition-based interpretation of information.…”
Section: Foreign Language Use May Improve News Discernmentmentioning
confidence: 99%
“…One is that several works have shown that information processed in a second language does not increase analytic thinking. For example, it does not improve performance on cognitive reflection tests (Costa, Foucart, Arnon, et al, 2014; Milczarski et al, 2022) nor in tasks involving conjunction fallacy or base rate neglect (Vives et al, 2018). It also does not improve detection of semantic illusions (Geipel et al, 2015b; but see Hadjichristidis et al, 2017).…”
Section: Preliminariesmentioning
confidence: 99%
“…For example, although people using their foreign language are indeed less aroused by the problem they face, this change in arousal was not predicting the decision change (Geipel et al, 2015b;Hadjichristidis et al, 2015;Muda et al, 2023). The second explanation also failed to be validatedpeople performed equally well (or, rather, equally bad) in the CRT in their foreign as in their native language (Milczarski et al, 2022). A third explanation that gained little attentionthat people use more abstract construals to represent a problemwas never directly tested.…”
Section: The Foreign Language Effectsmentioning
confidence: 99%